2023
DOI: 10.1155/2023/5334813
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and Typhoid Fever Coinfection among Febrile Patients in Ngaoundéré (Adamawa, Cameroon): A Cross-Sectional Study

Francky Steve Sohanang Nodem,
Didiane Ymele,
Mouni Fadimatou
et al.

Abstract: Background. Malaria and typhoid fever remain the major cause of morbidity and mortality in tropical and subtropical countries. It is common today to see patients being concurrently infected or treated for the two diseases. Objective. The aim of the present study was to determine the prevalence of malaria, typhoid fever, and their coinfection among febrile patients at Ngaoundéré Regional Hospital, Adamawa, Cameroon. Methodology. A cross-sectional and descriptive study was conducted on 208 febrile patients comin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Odikamnoro et al (2018) also recorded a slightly higher malaria/typhoid co-infection rate in females than in males. In Ngaoundéré (Adamawa, Cameroon), Sohanang et al (2023) reported that the female group and children from 2 to 10 years old were the most affected groups by the two infectious agents.…”
Section: Resultsmentioning
confidence: 99%
“…Odikamnoro et al (2018) also recorded a slightly higher malaria/typhoid co-infection rate in females than in males. In Ngaoundéré (Adamawa, Cameroon), Sohanang et al (2023) reported that the female group and children from 2 to 10 years old were the most affected groups by the two infectious agents.…”
Section: Resultsmentioning
confidence: 99%
“…Malaria symptoms include headaches, vomiting, fever, and lethargy. In severe situations, seizures, yellow skin, coma, or even death are possible results (Källander et al, 2004;Sohanang Nodem et al, 2023) In tropical developing nations, typhoid fever is a severe public health concern, particularly in areas with limited access to clean water and other sanitation measures (Nas et al, 2018). Low-and middle-income nations have a high Salmonella infection rate (>100 per 100,000 infected individuals annually) (Wilairatana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella Typhi-a Gram-Negative, oxidase-negative bacteria, through contaminated foods and water, causes typhoid fever known as acute systemic infection. Mohammad et al state that there are approximately 33 million cases of typhoid fever globally, with endemic areas accounting for 216,000 fatalities (Mohammed et al, 2020;Sohanang Nodem et al, 2023). Typhoid fever is caused by Salmonella enterica serotype typhi (S. typhi) and Salmonella enterica serotype paratyphi (S. paratyphi A, S. paratyphi B, and S. paratyphi C), with S. typhi been the most prevalent strain in causing typhoid fever (Crump, 2019).…”
Section: Introductionmentioning
confidence: 99%